Impact of Enzymes Supplementation (α- Amylase and Xylanase) in Diets Contains Corn and Wheat on Performance of Broiler Chickens - AL-JAF, Hardi Ahmed Karim; Kara, Muhammet Ali; Rashid, Saman Abdulmajid (Sulaimani Journal for Pure and Applied Sciences, 2018)
Birds are naturally output enzymes for digesting nutrients. However, birds does not have enzymes to moulder fiber perfectly and that enzymes secretion by salivary glands is very limited, especially to digesting high ratio of starch. So we need to add enzymes (α- Amylase and Xylanase) in the feed to aid digestion. The influence of enzyme supplementation on performance and digestibility in broiler chicks was examined for the diet containing corn and wheat with different levels of enzymes, while the diet containing corn and wheat, and adding enzymes of broiler chickes resulted significant (P≤0.05) increases in live body weight, weight gain, feed conversion and carcass weight, The best results for the traits included in this study were recorded by supplementing diet of broiler chicks with enzymes at the level of 0.04 % (T3, T6, and T9).
Keywords: Broiler; αamylase; xylanase; corn,wheat; performance